1991
DOI: 10.1097/00000658-199108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of (Regional) Total Pancreatectomy

Abstract: Little information has been reported on the metabolic characteristics of the totally pancreatectomized patient or the efficacy of medical management after radical pancreatic surgery. The prospective evaluation of 49 such patients, with 31% followed for 48 or more months, forms the basis of this report. The major immediate postoperative challenge is control of diarrhea and weight stabilization. Chronically patients have an increased daily caloric requirement (mean +/- SE, 56 +/- 1 kcal/kg), not wholly explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
5
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 54 publications
6
118
5
3
Order By: Relevance
“…pancreatic fistula. However, total pancreatectomy comes with its own set of complications in the form of permanent exocrine insufficiency and poorly controlled diabetes [52,53].…”
Section: Total Pancreatectomymentioning
confidence: 99%
“…pancreatic fistula. However, total pancreatectomy comes with its own set of complications in the form of permanent exocrine insufficiency and poorly controlled diabetes [52,53].…”
Section: Total Pancreatectomymentioning
confidence: 99%
“…In the past, TP led to obligate diabetes mellitus with frequent hypoglycaemic episodes [25][26][27] as well as the development of severe malabsorption due to exocrine insufficiency [25][26][27][28][29] . Moreover the procedure was associated with significant mortality and morbidity.…”
Section: Type Of Surgical Resectionmentioning
confidence: 99%
“…Therefore, long‐term metabolic complications have drawn considerable attention, and clinical studies have reported that hepatic steatosis occasionally occurs in patients who undergo PD 2, 3, 4, 5, 6, 7. This steatosis received little interest before the last decade because the patients did not usually have severe hepatic dysfunction clinically even though a few reports documented some cases of hepatic failure after pancreatic resection 8, 9, 10. The prevalence of this steatosis was reported to range from 7.8% to 37%,2, 3, 4, 5, 6, 11, 12 but a few reports are available on the time of occurrence and sequential change in the properties of this complication 13.…”
Section: Introductionmentioning
confidence: 99%